Are protein substitutes available in Italy for infants with inherited metabolic diseases all the same? - Di Costanzo, Margherita; Tosi, Martina; Muzi, Martina; Buono, Enrico Vito; D’Onghia, Valentina; Munerati, Anna; Tarditi, Gabriele; Bruni, Simone; Verduci, Elvira; Biasucci, Giacomo (Frontiers in Nutrition, 2025)
IntroductionInherited metabolic diseases (IMDs) represent a major clinical challenge, especially during the neonatal and infant periods. They require tailored and long-term nutritional management to ensure proper growth and development. Protein substitutes are essential in the dietary treatment of IMDs, particularly aminoacidopathies, organic acidemias, and urea cycle disorders. In Italy, a variety of PSs is available for infants with IMDs requiring a controlled protein and/or amino acid intake; however, differences in their nutritional composition may impact clinical outcomes. This study aims to examine and compare the nutritional composition of infant PSs (IPSs) available on the Italian market, focusing on macronutrients, micronutrients, and functional components.MethodsThe analysis targets products used in the dietary management of aminoacidopathies, organic acidemias, and urea cycle disorders during the first year of life. We compared the nutritional composition of products intended for healthy infants, considering the Commission Delegated Regulation (EU) 2016/127 and Commission Delegated Regulation (EU) 2016/128. Phenylketonuria is excluded from this analysis, as it has been recently addressed in another paper.ResultsFor each condition, there are only two products available, except for isovaleric aciduria and urea cycle disorders, which have only one product. The results indicate higher energy, linoleic, and alpha-linolenic acid content (+9%, +55%, and +290% compared to the maximum reference value), and lower levels of lactose, vitamin D, choline, selenium, and iodine (−92%, −34%, −37%, −12%, and −39% compared to the minimum reference value) for several IPSs. The analysis revealed the presence of docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) in all IPSs, while half of them contain arachidonic acid (ARA).DiscussionThis study represents the first comprehensive comparison of the nutritional profiles of IPSs for IMDs on the Italian market. The results identify potential areas for optimization, aiming to provide adequate levels of micronutrients, essential fatty acids, and functional ingredients, such as biotics, to support gut health, immune function, and neurodevelopment.